Membrane Potential Assessment by Fluorimetry as a Predictor Tool of Human Sperm Fertilizing Capacity - Baro Graf, Carolina; Ritagliati, Carla; Torres-Monserrat, Valentina; Stival, Cintia; Carizza, Carlos; Buffone, Mariano G.; Krapf, Dario (Frontiers in Cell and Developmental Biology, 2020)
Mammalian sperm acquire the ability to fertilize eggs by undergoing a process known as capacitation. Capacitation is triggered as the sperm travels through the female reproductive tract. This process involves specific physiological changes such as rearrangement of the cell plasma membrane, post-translational modifications of certain proteins, and changes in the cellular permeability to ions —with the subsequent impact on the plasma membrane potential (Em). Capacitation-associated Em hyperpolarization has been well studied in mouse sperm, and shown to be both necessary and sufficient to promote the acrosome reaction (AR) and fertilize the egg. However, the relevance of the sperm Em upon capacitation on human fertility has not been thoroughly characterized. Here, we performed an extensive study of the Em change during capacitation in human sperm samples using a potentiometric dye in a fluorimetric assay. Normospermic donors showed significant Em hyperpolarization after capacitation. Em values from capacitated samples correlated significantly with the sperm ability to undergo induced AR, highlighting the role of hyperpolarization in acrosomal responsiveness, and with successful in vitro fertilization (IVF) rates. These results show that Em hyperpolarization could be an indicator of human sperm fertilizing capacity, setting the basis for the use of Em values as a robust predictor of the success rate of IVF.